2018
DOI: 10.1017/s1041610218000327
|View full text |Cite
|
Sign up to set email alerts
|

Convergent and concurrent validity of a report- versus performance-based evaluation of everyday functioning in the diagnosis of cognitive disorders in a geriatric population

Abstract: In contrast to prior studies comparing report-based and performance-based methods of assessing ADL, this study indicates that the NAT and the a- and i-ADL tools have strong convergent and concurrent validity, and appear to have similar discriminatory power in differentiating between HCs, MCI, and AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…This could be debated since report‐based measures are often considered as not being as accurate as performance‐based evaluations because of lacking sound psychometrical properties and possible overestimation and underestimation of functional ability . However, it is shown in previous studies that the b‐, i‐, and a‐ADL tools might compete with performance‐based tools . In addition, a recent meta‐analysis investigating different methods of assessing ADLs indicated that all methods are moderately correlated with EF .…”
Section: Discussionmentioning
confidence: 99%
“…This could be debated since report‐based measures are often considered as not being as accurate as performance‐based evaluations because of lacking sound psychometrical properties and possible overestimation and underestimation of functional ability . However, it is shown in previous studies that the b‐, i‐, and a‐ADL tools might compete with performance‐based tools . In addition, a recent meta‐analysis investigating different methods of assessing ADLs indicated that all methods are moderately correlated with EF .…”
Section: Discussionmentioning
confidence: 99%
“…Total score ranges from zero to 23 (Vittengl et al, 2006). The Lawton scale showed significantly higher scores for MCI participants compared to mild Alzheimer's disease participants (Cornelis et al, 2018). This questionnaire was also found effective in MCI diagnosis among Italian (Di Carlo et al, 2007) and Brazilian (de Paula et al, 2014) elderly.…”
Section: Instrumentsmentioning
confidence: 92%
“…Informant-based or performance-based measures could be more reliable. However, in a previous study on ADLs in cognitive disorders, it was already showed that both report-based and performance-based measures have similar discriminatory power, but this needs to be further investigated in frailty (Cornelis et al, 2018). However, the study is unique in the sense that we included a large sample size of older individuals aged 80 years and over, the fastest growing population group.…”
Section: Discussionmentioning
confidence: 98%